3D Ultrasonography to Evaluate Fetal Urinary Production Rates in Twin Gestation: Construction of a Normal Value Curve. (February 2014) - Mocarzel, Carolina Carvalho; de Sá, Renato Augusto Moreira; Velarde, Luis Guillermo Coca; Peixoto-Filho, Fernando Maia; Ville, Yves
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: The aim of this study was to assess fetal urinary production rates (FUPR) in twin gestations using 3D ultrasonography with VOCAL® (virtual organ computer-aided analysis) and to develop a curve of normal values for the target population. Methods: A cross-sectional study was performed in 30 normal twin pregnancies with gestational ages ranging from 20 to 34 weeks. FUPR was measured using a three-dimensional ultrasound (3D US) virtual organ computer-aided analysis (VOCAL) system. FUPR (ml/hour) was calculated during the filling phase using the equation UPR = (VFB2 - VFB1)/time. The values for UPR were plotted as a function of fetal biometry (biparietal diameter) to generate a nomogram. Results: A total of 41 normal twin fetuses with gestational ages between 20 and 34 weeks were investigated. Eleven were excluded because of inadequate bladder contour image quality and/or the observation of micturition in one or both fetuses. Linear regression analysis of FUPR as a function of biparietal diameter (BPD) shows the normal range for UPR by fetal biometry and is expressed by the following equation: Ln(UPR) = -5.0121 + 0.0548 BPD (R2 0.3386, p value <.001). There was no statistically significant difference when the UPR was stratified by chorionicity. Conclusions: The use of biometric parameters to predict fetal FUPR seems to be useful. In twin pregnancies, BPD is the variable that is most closely related to FUPR. For each 1 mm increase in BPD, there is a 5% increase in FUPR. Chorionicity did not affect FUPR.